Bone Wax: A Foreign Body/Giant Cell Reaction in the Foot. Issue 3 (June 2013) - Hill, Josh; Little, Jessica; Ford, Tim
Bone wax has been used for years by surgeons as a hemostatic agent to prevent bleeding from bone surfaces. Though the effectiveness of bone wax as a hemostatic agent while acting as a tamponade is well known, it is not without its complications. It has been documented in the medical literature that bone wax may remain in the body for many years as a foreign body and in some cases cause a giant cell reaction at various surgical sites. However, to the authors' knowledge, there has not been a reported case of a foreign body giant cell reaction secondary to the use of bone wax in the current podiatric literature. Two case studies are described to bring attention to the fact that bone wax can interfere with bone healing while remaining attached to bone as a foreign body and induce a giant cell reaction and local inflammatory effects in the human foot. Levels of Evidence: Therapeutic, Level IV, Case Study